The Philosophy-Ladenness of Perception: A Philosophical Analysis of Perception in Husserl and Sartre - Mika Suojanen (Addleton Academic Publishers, 2022)
The basic entity in phenomenology is the phenomenon. Knowing the phenomenon
is another issue. The phenomenon has been described as the real natural object or
the appearance directly perceived in phenomenology and analytic philosophy of perception.
Within both traditions, philosophers such as Husserl, Heidegger, Merleau-Ponty, Russell and
Wittgenstein have considered that perceptual experience demonstrates what a phenomenon
is on the line between the mind and the external world. Therefore, conceptualizing the
phenomenon is based on the perceptual evidence. However, if the belief that perception is
“theory-laden” is true, then perception can also be “philosophy-laden.” These philosophers
have not noticed whether perceptual knowledge is independent of philosophies. If perceptual
knowledge is not independent of philosophies, a philosopher’s background philosophy
can influence what he or she claims to know about the phenomenon. For Husserl, experience
is direct evidence of what exists. The textual evidence shows that Sartre rejects the
distinction between appearance and reality based on the assumption of the phenomenon. By
examining Husserl’s Ideas and Sartre’s Being and Nothingness I conclude that these
philosophers’ philosophical languages influence their perceptual knowledge. Philosophical
traditions affect the thoughts of perception.